Կերպարակերտման առանձնայատկութիւնները Լեւոն Բաշալեանի արձակում - Անդրէասեան, Թամարա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
The article touches upon the peculiarities of character development in the works of Levon Bashalian. Drawing on the insights of analytical psychology, we have conducted a psychological and profound analysis of characters, as evidenced by the works of Z. Freud and K. G. Jung. The article delves into numerous issues, shedding light on them through the lens of contemporary literary studies. Various approaches have been employed to examine the psychological traits of the protagonists depicted in novels and short stories։ • The actions of characters demonstrating depressive and isolated traits in social relationships were elucidated through an examination of the impact of the social environment and individual characteristics. • For behavioral analysis of characters, the portrait with a socio-psychological and national layer was employed to enhance the comprehensive psychological depiction of the character. • Special attention was given to the description of the physical environment and natural phenomena, serving as a means to gain psychological insights. В статье затрагиваются особенности создания образов Левона Башаляна. С целью глубокого, психологического анализа образов нами был использован опыт аналитической психологии, ссылаясь на взгляды З. Фрейда, К. Юнга. Многие вопросы в статье трактуются исходя из современного литературоведческого опыта. Черты душевного склада героев, встречающихся в новеллах и рассказах, были рассмотрены по нескольким методам: • Действия образов, которые в общественных отношениях демонстрируют подавленные, изолированные черты характера, обусловлены ролью социальной среды и личностными свойствами. • Для поведенческого анализа образов был использован портрет — с национальными, социально-психологическими слоями, что помогло обобщить психологическое описание характера. • Подчеркивается значимость описания социума, окружающей среды, природных явлений, через которые возможны психологические проникновения.
Keywords: Բանասիրութիւն